A development of smart village implementation plan for agriculture: A pioneer project in Malaysia - Abdul Razak, Norizan; Abdul Malik, Jalaluddin; Saeed, Murad (2013)
The current study mainly aimed to investigate the Malaysian Smart Village project in a rural community which is labeled as Kg Besting in Malaysia.Specifically, the study intended to address the major issues faced by the community of farmers, identify the Smart Village indicators and put forward a strategic plan for the Smart Village implementation.It was carried out among Malaysian farmers in Kg Besting community in Malaysia.Data was collected through a survey, focus group interviews and documents.The quantitative and qualitative analyses of the data revealed that the major issues faced by the farmers in this community in agriculture are limited involvement of human capital in agricultural activities, the small size of land and limited knowledge of using technologies and innovative techniques to enhance the agricultural processing and production.Other issues are relevant to Micro Small Medium Entrepreneurs (SMMEs) in Kg Besting include lack of raw materials and crops, lack of machinery, limited knowledge and lack of advice and networking on how to ensure mass production and healthy marketing competition at the regional and global levels. Thus, the study emphasizes the importance of meeting the community‘s needs in Kg Besting and offers several useful recommendations.In conclusion, by incorporating the concept of ―Smart Village‖, the current study considers the potential Smart Village as an innovative means of improving rural people‘s life and it introduces a strategic implementation of the Smart Village project in Kg Besting in three phases; social empowerment, developing the Smart Village ecosystem and economic empowerment